2015
DOI: 10.1039/c5ra08887a
|View full text |Cite|
|
Sign up to set email alerts
|

Rhodium-catalyzed synthesis of quinolines and imines under mild conditions

Abstract: An environmentally benign protocol for the synthesis of quinolines in aqueous medium by using Rh(II)acetate/TPPTS recyclable catalytic system has been developed. The anilines were reacted smoothly with allyl alcohols furnishing the corresponding quinolines in moderate to good yields. This 10 catalytic system was recycled up to five runs without much loss in its catalytic activity. Furthermore, imines were also synthesized from benzylamines in moderate to good yields.A simple and efficient protocol for the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…88 In 2015, Bhanage and coworkers found that the quinolines 157 could be synthesized from anilines and allyl alcohol 156 using Rh 2 (OAc) 4 and tri- phenylphosphine trisulfonate sodium salt (TPPTS) as the catalysts in a simple but efficient manner (Scheme 49). 89 Remarkably, this reaction was conducted in water and the catalyst could be recycled up to five runs without much loss in its catalytic activity. Mechanistically, dirhodium hydride-mediated isomerization of allyl alcohol to the corresponding propanal was involved.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…88 In 2015, Bhanage and coworkers found that the quinolines 157 could be synthesized from anilines and allyl alcohol 156 using Rh 2 (OAc) 4 and tri- phenylphosphine trisulfonate sodium salt (TPPTS) as the catalysts in a simple but efficient manner (Scheme 49). 89 Remarkably, this reaction was conducted in water and the catalyst could be recycled up to five runs without much loss in its catalytic activity. Mechanistically, dirhodium hydride-mediated isomerization of allyl alcohol to the corresponding propanal was involved.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%